Measuring Economic Uncertainty with Artificial Intelligence - Romih, Dejan; Dajčman, Silvo (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
Artificial intelligence has an impact on all areas and aspects of social life. In this paper, we analyse the measurement of economic uncertainty with artificial intelligence. To do so, we use the Stanford Cable TV News Analyzer, which allows us to analyse cable news on CNN, FOX and MSNBC. Using this tool, we have developed three cable news-based economic uncertainty indices that complement existing economic uncertainty indices and allow for more in-depth exploration of this area of research. Using a vector autoregression model, we found that a shock to economic uncertainty coverage by individual cable news channels has different effects on the US economy.